Translation, linguistics, culture : a French-English handbook - Armstrong, Nigel (Nigel Robert) (Topics in translation, 2005)
This book takes a linguistic approach to translation issues, looking first at the structural view of language that explains the difficulty of translation and at theories of cultural non-equivalence. A subsequent chapter on text types, readership and the translator's role completes the theoretical framework.